Long-term morbidity after surgery for perihilar cholangiocarcinoma: A cohort study. (December 2022) - Gilbert, Timothy M.; Hackett, James; Holt, Lauren; Bird, Nicholas; Quinn, Marc; Gordon-Weeks, Alex; Diaz-Nieto, Rafael; Fenwick, Stephen W.; Malik, Hassan Z.; Jones, Robert P.
Abstract: Background: Surgery for perihilar cholangiocarcinoma (pCCA) offers the only possibility of long-term survival, but remains a formidable undertaking. Traditionally, 90-day post-operative complications and death are used to define operative risk. However, there is concern that this metric may not accurately capture long-term morbidity after such complex surgery. Methods: A retrospective review of a prospective database of patients undergoing surgery for pCCA at a Western centre between January 2009-2020. Results: Eighty-five patients underwent surgical resection for pCCA with a median overall survival of 36.3 months. Post-op (<90day) morbidity rates were high with 46% of patients developing a major complication (Clavien-Dindo grade 3–4). Post-op mortality rate was 13%. In total 38% (28/74) of patients experienced at least 1 episode of delayed morbidity (>90-days of surgery) resulting in 53 separate admissions with a median LOS of 7 days (IQR 2–15). These episodes were predominately secondary to biliary obstruction with the majority requiring radiological intervention (Clavien-Dindo grade 3). The development of long-term morbidity was associated with increased recurrence rates and correlated with poorer OS (27.6 months vs. 65.7 months HR 2.2 CI 1.63-2.77). Conclusions: Routinely cited 90-day morbidity and mortality does not accurately capture the patient morbidity experienced following surgery for pCCA. Surgery clearly offers a survival benefit and should be pursued in selected patients, but they must be fully counselled on the potential for long-term morbidity before embarking on this strategy. Highlights: Surgery for hilar cholangiocarcinoma has significant morbidity and mortality. Patients undergoing surgery are at risk of developing long-term morbidity. Long-term morbidity is associated with increased recurrence rates and poor survival. Patients should be counselled on risk of long-term morbidity prior to surgery.